Applying Translational Science Approaches to Protect Workers Exposed to Nanomaterials - Schulte, Paul A.; Guerin, Rebecca J.; Cunningham, Thomas R.; Hodson, Laura; Murashov, Vladimir; Rabin, Borsika Adrienn (Frontiers in Public Health, 2022)
Like nanotechnology, translational science is a relatively new and transdisciplinary field. Translational science in occupational safety and health (OSH) focuses on the process of taking scientific knowledge for the protection of workers from the lab to the field (i.e., the worksite/workplace) and back again. Translational science has been conceptualized as having multiple phases of research along a continuum, beyond scientific discovery (T0), to efficacy (T1), to effectiveness (T2), to dissemination and implementation (D&I) (T3), to outcomes and effectiveness research in populations (T4). The translational research process applied to occupational exposure to nanomaterials might involve similar phases. This builds on basic and efficacy research (T0 and T1) in the areas of toxicology, epidemiology, industrial hygiene, medicine and engineering. In T2, research and evidence syntheses and guidance and recommendations to protect workers may be developed and assessed for effectiveness. In T3, emphasis is needed on D&I research to explore the multilevel barriers and facilitators to nanotechnology risk control information/research adoption, use, and sustainment in workplaces. D&I research for nanomaterial exposures should focus on assessing sources of information and evidence to be disseminated /implemented in complex and dynamic workplaces, how policy-makers and employers use this information in diverse contexts to protect workers, how stakeholders inform these critical processes, and what barriers impede and facilitate multilevel decision-making for the protection of nanotechnology workers. The T4 phase focuses on how effective efforts to prevent occupational exposure to nanomaterials along the research continuum contribute to large-scale impact in terms of worker safety, health and wellbeing (T4). Stakeholder input and engagement is critical to all stages of the translational research process. This paper will provide: 1) an illustration of the translational research continuum for occupational exposure to nanomaterials; and 2) a discussion of opportunities for applying D&I science to increase the effectiveness, uptake, integration, sustainability, and impact of interventions to protect the health and wellbeing of workers in the nanotechnology field.